PD.185 Oral cancer and precancer researchin Malaysia — the database and tissue resource bank - Zain, R.B.; Latifah, R.J.R.; Razak, I.A.; Ismail, S.M.; Samsuddin, A.R.; Atiya, S.A.; Hashim, B.Y.; Jallaludin, A.; Nasir, W.M.; Cheong, S.C.; Bustam, A.Z.; Mahadzir, W.M.W.; et al. (Elsevier, 2005)
Introduction: Uncoordinated data collection by different research groups prompted the initiation of Malaysian oral cancer Research Initiative (MOCRI) group. Objectives: To coordinate and standardize data and tissue collection and storage, develop a minimum dataset on risk factors, intervention techniques and quality of life of oral cancer patients. Materials and Methods: A computer software programme is currently being developed to accommodate multi-centre data collection and research activities in eight hospitals. The complete dataset includes parameters on sociodemographic, clinical, pathological, quality of life measures, details of treatment methods, vital status and dietary intake. Tissues are being collected, stored and catalogued as fresh and formalin-fixed tissues for future use in satellite researches. The networking in tissue and data collection includes the establishment of oral cancer cell-lines. These tissues are being planned for studies on genetic profile, genetic polymorphism, diagnostic and prognostic markers. Results: Tissues and data on 115 oral cancers, 9 leukoplakia and 13 lichen planus has been collected since 2003. Preliminary data from 2004 were analysed for 58 cancer patients. Majority of them are more than 60 years old (65.5%) with a mean age of 63.3. Twenty-four (41.4%) were males, 34 (58.6%) females with the majority of them being Indians (56.9%) followed by Chinese and Malays (15.5% each), Indigenous people of Sabah and Sarawak (12.1%). Eighteen (31%) respondents were smokers, 17 (29.3%) alcohol drinkers and 31 (53.4%) betel quid chewers. Five patients have had histories of family cancers where 3 included immediate family members with head and neck cancers. For the quality of life measure, only 30.2% felt that their daily activities were disrupted despite having advanced cancers. Satellite researches are in progress on genetic polymorphism and tumour markers. One oral cancer cell-line has been established. Conclusion: The establishment of oral cancer database and tissue bank in encouraging and supports on-going satellite researches.